2018
DOI: 10.15381/rivep.v29i2.14482
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización de microorganismos con potencial probiótico aislados de estiércol de terneros Brahman en Sucre, Colombia

Abstract: El objetivo del estudio fue caracterizar microorganismos con potencial probiótico de estiércol de terneros lactantes Brahman en Sucre (Colombia). Se aislaron bacterias y levaduras de las muestras de estiércol y se determinó la capacidad probiótica de estas cepas mediante pruebas de resistencia a sales biliares (0.05, 0.1, 0.15 y 0.3%), resistencia a pH ácido (pH 3, 4, 5.6, 7), tolerancia a NaCl (2, 4, 6, 8, 10%) y actividad antagónica (Salmonella sp y Escherichia coli). Nueve microorganismos fueron identificad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
2
3
0
2
Order By: Relevance
“…In particular, the physiological pH range in the rumen has been reported to be between 5.5 and 6.9 (Choudhury et al, 2015 ). In keeping with this, all the BC we evaluated in MNA broth had the optimum development at a similar pH range of 6.5 and 7 at 24 and 48 h. This same pattern was also found in other works in which the highest bacterial growth was shown to occur at pH close to 7 with a significant decrease at acidic pH (Ávila et al, 2010 ; Bertel et al, 2019 ; Castillo et al, 2018 and Landa‐Salgado et al, 2019 ). Moreover, Marrero et al ( 2010 ) evaluated different strains of bacilli and reported high growth of cellulolytic bacteria at pH at the rumen level of 6.6.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In particular, the physiological pH range in the rumen has been reported to be between 5.5 and 6.9 (Choudhury et al, 2015 ). In keeping with this, all the BC we evaluated in MNA broth had the optimum development at a similar pH range of 6.5 and 7 at 24 and 48 h. This same pattern was also found in other works in which the highest bacterial growth was shown to occur at pH close to 7 with a significant decrease at acidic pH (Ávila et al, 2010 ; Bertel et al, 2019 ; Castillo et al, 2018 and Landa‐Salgado et al, 2019 ). Moreover, Marrero et al ( 2010 ) evaluated different strains of bacilli and reported high growth of cellulolytic bacteria at pH at the rumen level of 6.6.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, the relative species abundance based on DNA sequences of potential probiotic BC showed that all of those cultured in MRS belong to the phylum Firmicutes and all of them to the class Bacilli , whereas the BC cultured in MNA broth belong mainly to the phylum Proteobacteria (class Grammaproteobacteria ) (data not shown). Castillo et al ( 2018 ) and Bertel et al ( 2019 ), as in our study, identified Enterococcus and Bacillus in samples with the best results in the probiotic tests. Zhou et al ( 2015 ) found that in ruminal populations the most abundant phyla always fell on Firmicutes and Bacteroidetes .…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, Pichia kudriavzevii has been reported to produce inhibition halos of 8.56 and 9.50 mm for E. coli and Salmonella sp, demonstrating that it produces antimicrobial substances capable of counteracting these pathogens in vitro. (29)…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…On the other hand, Pichia kudriavzevii has been reported to produce inhibition halos of 8.56 and 9.50 mm for E. coli and Salmonella sp, demonstrating that it produces antimicrobial substances capable of counteracting these pathogens in vitro. (29) The antibacterial activity of kefir can be due to a variety of factors, starting with proteolytic enzymes, organic acids, CO2, bacteriocins, bioactive peptides, as well as competition for nutrients and the generation of antibacterial compounds during carbohydrate metabolism by lactic acid bacteria. In addition, decreased pH of kefir due to accumulation of organic acids leads to broad-spectrum inhibitory activity against Gram-positive and Gram-negative bacteria.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…) Castillo et al (2018). aislaron y determinaron el potencial probiótico de la cepa de levadura identificada molecularmente como C. krusei (Castellani) Berhout (Saccharomycetes: Pichiaceae), que tuvo mejorRicardo Enrique, López Barreto; et al …”
unclassified